The hierarchical and perturbative forms of stochastic Schrödinger equations and their applications to carrier dynamics in organic materials. (24th July 2018) - Wang, Yu‐Chen; Ke, Yaling; Zhao, Yi
Abstract : A number of non‐Markovian stochastic Schrödinger equations, ranging from the numerically exact hierarchical form toward a series of perturbative expressions sequentially presented in an ascending degrees of approximations are revisited in this short review, aiming at providing a systematic framework which is capable to connect different kinds of the wavefunction‐based approaches for an open system coupled to the harmonic bath. One can optimistically expect the extensive future applications of those non‐Markovian stochastic Schrödinger equations in large‐scale realistic complex systems, benefiting from their favorable scaling with respect to the system size, the stochastic nature which is extremely suitable for parallel computing, and many other distinctive advantages. In addition, we have presented a few examples showing the excitation energy transfer in the Fenna‐Matthews‐Olson complex, a quantitative measure of decoherence timescale of hot exciton, and the study of quantum interference effects upon the singlet fission processes in organic materials, since a deep understanding of both mechanisms is very important to explore the underlying microscopic processes and to provide novel design principles for highly efficient organic photovoltaics. This article is categorized under: Theoretical and Physical Chemistry > Reaction Dynamics and Kinetics Structure and Mechanism > Computational Materials Science Abstract : The TOC shows that two kinds of non‐Markovian stochastic Schrodinger equations, namely the hierarchical and the perturbative forms, as well as their applications to explore the carrier dynamics in organic materials are reviewed in this paper.